A Rapid Route to Aminocyclopropanes via Carbamatoorganozinc Carbenoids1. Issue 38 (1st August 2013) - Ishikawa, Shingo; Sheppard, Tom D.; D'Oyley, Jarryl M.; Kamimura, Akio; Motherwell, William B.
<x xml:space="preserve">Abstract</x> Easy as 1, 2, 3: Reaction of methyl carbamate, triethyl orthoformate, and readily available alkenes provides a highly practical preparation of protected aminocyclopropanes. The reaction proceeds with preferential cis addition to alkenes, and cleavage of the methyl carbamate gives the free aminocyclopropanes as their HI salts (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>